Factors Hindering Effective Online Learning among Undergraduate Office Administration Education Students - Andi Agung; Muh Darwis; Nasaruddin Nasaruddin (Journal of Educational Development and Learning (JEDAL), 2026)
Online learning refers to instructional activities conducted through digital networks where interaction, content delivery, and evaluation are mediated by technology. In the implementation of online learning, it is not free from obstacles faced. Obstacles to online learning are various obstacles or difficulties experienced by students, lecturers, and related parties in the teaching and learning process conducted online. The purpose of this study is to determine how the obstacles to online learning of students of the Office Administration Education Undergraduate study program, Faculty of Social Sciences and Law, Makassar State University. The type of research used in this study is descriptive qualitative research and data collection techniques used are observation, interviews, and documentation techniques, then analyzed by reduction, presentation, and verification. Indicators used in this study are management and implementation of learning, communicative teaching and learning process, student responses, learning activities, and learning outcomes. The results of the study indicate that the Analysis of Obstacles to Online Learning of Students of the Office Administration Education Undergraduate Study Program, Faculty of Social Sciences and Law, Makassar State University is in the fairly good category. It is shown in the aspects of management and implementation of learning, which have been running but still encounter obstacles including media, and internet network disruptions. In the communicative teaching and learning process, it can be considered adequate, as reflected in the interaction between learning parties has been implemented but has not run optimally. Student responses show a tendency to decrease learning motivation due to unsupportive environmental situations and conditions. Learning activities are less effective due to limited direct supervision and monotonous routines. Meanwhile, learning outcomes are not optimal due to obstacles in understanding the material and limited feedback received. Thus, overall, the Analysis of Obstacles to Online Learning for Students of the Undergraduate Study Program in Office Administration Education, Faculty of Social Sciences and Law, Makassar State University has run quite well, although improvements are still needed in several aspects.